Rare bird documentation form for Northern Goshawk at Sweet Marsh in 1982 - Myers, Robert K.et al (1982)
Rare bird documentation form for a Northern Goshawk at Sweet Marsh in Bremer County, IA on November 14, 1982. Epson - sheet feed